Establishment of an olfactory region-specific intranasal delivery technique in mice to target the central nervous system - Flamm, Johannes Eberhard; Hartung, Sunniva; Gänger, Stella; Maigler, Frank; Pitzer, Claudia; Schindowski, Katharina (Frontiers in pharmacology, 2022)
We have recently developed a region-specific catheter-based intranasal application method in mice by using CT scan-based 3D cast models of the murine nose (DOI: 10.2376/0005-9366-17,102). This technique is able to specifically deliver drugs to the olfactory region or to the respiratory region only. Thereby, intranasally administered drugs could be delivered either via neuronal connections to the central nervous system or via the well-perfused rostral parts of the nasal mucosa to the systemic circulation. In the present study, we transferred successfully this novel delivery technique to C57Bl/6 mice and determined parameters such as insertions depth of the catheter and maximum delivery volume in dependence to the weight of the mouse. Breathing was simulated to verify that the volume remains at the targeted area. A step-by-step procedure including a video is presented to adopt this technique for standardized and reproducible intranasal central nervous system (CNS) delivery studies (DOI: 10.3390/pharmaceutics13111904).
Gesehen am 12.09.2022